Reconstructing Ethical Leadership through Kresnayana Traditional Performance: A Culturally Responsive Project-Based Character Education Model - Jamila Wijayanti; Muh. Fatoni Rohman; Muhammad Hambali; Maulfi Syaiful Rizal (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Ethical leadership has become an increasingly important concern as educational institutions seek effective approaches to cultivate students' moral responsibility alongside academic competence. Although character education has been widely implemented, limited attention has been given to transforming indigenous cultural heritage into authentic learning experiences that foster ethical leadership. This study explores the leadership values embodied in the Kresnayana traditional dance drama and examines their integration into the Projek Penguatan Profil Pelajar Pancasila (P5) through a Project-Based Learning framework. A qualitative study employing a realist ethnographic approach was conducted in Blitar Regency, Indonesia, involving 21 purposively selected participants, including cultural practitioners, educators, policymakers, and students. Data were collected through participant observation, semi-structured interviews, and document analysis, and analyzed using thematic analysis supported by triangulation and member checking. The findings reveal three interconnected leadership values wisdom, humanism, and integrity that were progressively internalized through four learning stages: value exploration, critical reflection, collaborative artistic performance, and reflective evaluation. These experiences encouraged students to develop ethical awareness, collaborative competence, cultural identity, and leadership responsibility in authentic educational settings. This study contributes to the ethical leadership and character education literature by demonstrating how local cultural traditions can be transformed into culturally responsive pedagogical practices. The proposed model offers practical guidance for integrating indigenous knowledge into contemporary school curricula while strengthening sustainable character education.